Quick-curing bio-based hot melt adhesive and preparation method thereof

By combining modified polyetheramine and dimeric acid and other raw materials, fast-solid bio-based hot melt adhesive was prepared, which solved the problem of deterioration of the flexibility of the hot melt adhesive in a low-temperature environment, achieved good low temperature resistance and self-healing properties, and met the high-standard bond strength and durability requirements.

CN119823711AActive Publication Date: 2025-04-15ZHEJIANG AOYU NEW MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510309683.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The flexibility of existing hot melt adhesives has dropped sharply in low temperature environments and is prone to brittle cracking. Moreover, bio-based hot melt adhesives are difficult to meet the needs of high standards in terms of bonding strength and low temperature resistance.

Method used

The polyetheramine is modified by using cyclosiloxane, thiol acid and polyetheramine as raw materials, and mixed with dimeric acid, sebacic acid, antioxidant, catalyst, organoborosiloxane and stearic acid to prepare a fast-solid bio-based hot melt adhesive.

Benefits of technology

The prepared hot melt adhesive has good low temperature resistance, viscosity and self-healing properties, which significantly improves its performance in low temperature environments and meets the requirements of high standards of bond strength and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of hot melt adhesives, and particularly relates to a quick-curing bio-based hot melt adhesive and a preparation method thereof. Cyclosiloxane, mercapto acid and polyether amine are used as raw materials, siloxane modified polyether amine is obtained through ring opening polymerization, mercapto-alkene click reaction and amidation reaction, then siloxane modified polyether amine is mixed with dimer acid, sebacic acid, an antioxidant, a catalyst, organic borosiloxane and stearic acid, and the quick-curing bio-based hot melt adhesive is obtained. The prepared hot melt adhesive has good low temperature resistance, viscosity and self-healing property, and the dimer acid is used as a main bio-based raw material, so that the hot melt adhesive has good biodegradability and is environmentally friendly and sustainable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hot melt adhesive preparation, and specifically relates to a fast-curing bio-based hot melt adhesive and a preparation method thereof. Background Art

[0002] Hot melt adhesive is a solvent-free adhesive made of thermoplastic polymer as the base material, with the addition of tackifying resin, wax and antioxidant and other ingredients, and prepared by melt blending. Compared with traditional solvent-based adhesives and inorganic adhesives, it has the advantages of no volatile organic compounds, water resistance, fast curing speed and repeatable bonding, and is easy to process, recyclable, and has high automation and low cost. Hot melt adhesives can generally be divided into ethylene, polyamide, polyester, polyurethane and thermoplastic rubber. Polyamide resin hot melt adhesive is widely used in industrial production. It is formed by the condensation of dibasic acid and diamine or polyamine. Dimer acid polyamide resin is a kind of polyamide resin, which is obtained by the condensation reaction of dimer acid and diamine or polyamine. Dimer acid is generally a polymer synthesized by heating and catalysis of two identical or different unsaturated fatty acids with 18 carbon atoms, and the raw materials can also be obtained from renewable resources. As people's environmental awareness continues to increase, low-pollution or pollution-free environmentally friendly hot melt adhesives have received attention from the industry. Therefore, the development of more environmentally friendly adhesives with a wider range of applications is of great significance to the development of the adhesive industry.

[0003] A Chinese patent with announcement number CN115725259B discloses a reactive polyurethane hot melt adhesive and a preparation method thereof, which is prepared by mixing polyether polyol, polyester polyol, tackifying resin, thermoplastic resin, polyisocyanate, adhesion promoter and catalyst. The polyether polyol is modified by using polysiloxane, and polysiloxane molecular chains are introduced to enhance the mutual sliding ability of the molecular chains of the PUR adhesive, thereby effectively improving the initial adhesion performance of the product. The characteristics of the curled and helical conformation of the polysiloxane molecular chains make the prepared hot melt adhesive have excellent fatigue resistance. A Chinese patent with announcement number CN115851213B discloses a reactive polyurethane hot melt adhesive for bonding nitrile rubber and a preparation method thereof. The adhesive is prepared by mixing crystalline polyester polyol, liquid polyester polyol, dimer acid-modified polyol, isocyanate, adhesion promoter, hydroxy-terminated nitrile rubber, catalyst, carbon black and antioxidant. By adding an appropriate amount of dimer acid-modified polyol, the polyol has better wettability with NBR, so that PUR has better adhesion to NBR. The reactive polyurethane hot melt adhesive for bonding nitrile rubber can obtain excellent bonding strength in NBR material bonding applications without surface treatment of the NBR material, which can greatly improve the bonding efficiency of the NBR material and reduce costs.

[0004] However, with the continuous development of hot melt adhesives, their application environment has become more and more complex, thus putting forward higher requirements for the preparation of weather-resistant hot melt adhesives, especially low-temperature-resistant hot melt adhesives. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a fast-curing bio-based hot melt adhesive and a preparation method thereof. Cyclosiloxane, mercapto acid and polyetheramine are used as raw materials, and siloxane-modified polyetheramine is obtained through ring-opening polymerization, mercapto-ene click reaction and amidation reaction. The siloxane-modified polyetheramine is then mixed with dimer acid, sebacic acid, an antioxidant, a catalyst, organoborosiloxane and stearic acid to obtain the fast-curing bio-based hot melt adhesive. The prepared hot melt adhesive has good low-temperature resistance, adhesion and self-healing properties.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows: A method for preparing a fast-curing bio-based hot melt adhesive comprises the following steps: S1, obtaining a polysiloxane with a branched vinyl structure by a ring-opening polymerization reaction of cyclosiloxane; S2, polysiloxane with branched vinyl structure and mercapto acid are reacted by mercapto-ene click reaction to obtain polysiloxane containing alkyl branches; S3, alkyl branched polysiloxane and polyetheramine are subjected to amidation reaction to obtain siloxane-modified polyetheramine; S4, adding dimer acid, sebacic acid, siloxane-modified polyetheramine, antioxidant and catalyst into the reaction kettle, stirring and heating to 110-130°C, stirring rate of 200-300rpm, turning off the heating when adding ethylenediamine, allowing it to heat up naturally, ethylenediamine is added dropwise, the dropwise addition time is controlled for 50-70min, the temperature is controlled at 130-150°C, after the addition is completed, the temperature is controlled at 130-150°C for 1-2h, and then the temperature is increased to 230-250°C for 20-40min; Dimer acid is used as the main bio-based raw material, which provides a good flexible adhesion foundation. The addition of sebacic acid helps to adjust the structure and performance of the molecular chain. The antioxidant can effectively prevent the oxidative degradation of the material during processing and use. The catalyst can promote the efficient progress of the reaction. The slow dripping of ethylenediamine is different from the traditional one-time mixing or rapid dripping, which can avoid the problems of increased side reactions, unstable product performance and gelation due to excessive local reaction. The molecular weight distribution of the polymer can be effectively regulated by accurately controlling the dripping speed and temperature, thereby significantly improving the mechanical properties of the hot melt adhesive. After the dripping is completed, the temperature is controlled to continue to be kept warm, which provides enough time for the reaction, so that the reactants can further react fully, promote the growth and cross-linking of the molecular chain, improve the uniformity and stability of the product, and ensure the consistency of the performance of the prepared hot melt adhesive. The temperature is further increased and kept warm for a period of time. The reaction is carried out at a higher temperature, which is conducive to forming a more complete polymer network structure and enhancing the interaction between molecules, thereby giving the hot melt adhesive high mechanical strength. S5. After the heat preservation is completed, vacuum polymerization is carried out. After the polymerization is completed, nitrogen is used to break the air, and the temperature is lowered to discharge the material to obtain a polymer. The vacuum operation can effectively remove small molecules such as water and unreacted monomers in the reaction system, which can effectively improve the purity of the product, reduce the adverse effects of impurities on product performance, help form a denser polymer structure, and further improve the performance of the hot melt adhesive product. S6. Add the polymer and organoborosiloxane into a reaction kettle, heat to 110-130° C., stir and react for 1-3 hours, add stearic acid and control the vacuum degree, vacuum and stir for 20-40 minutes, cool and discharge, and obtain the fast-curing bio-based hot melt adhesive.

[0007] Hot melt adhesive is a solid adhesive composed of thermoplastic polymers, antioxidants, etc. Hot melt adhesive can be divided into high temperature, medium temperature and low temperature hot melt adhesive according to the use temperature. Hot melt adhesive is widely used in people's daily life, but with the increasingly complex and diverse use environment, traditional hot melt adhesive faces the problem of sharp decline in flexibility and easy brittle cracking in low temperature environment, which seriously affects the scope of use of hot melt adhesive. At the same time, with the continuous enhancement of environmental awareness, the industry has an urgent need for the research and development of bio-based hot melt adhesive. Therefore, in the present invention, dimer acid is used as a bio-based raw material and mixed with sebacic acid, polyamide, ethylenediamine, etc. to prepare hot melt adhesive, but bio-based hot melt adhesive is difficult to meet high standards in terms of bonding strength and low temperature resistance. Therefore, in the preparation process, polyether amine is modified with siloxane to improve the flexibility, low temperature resistance and adhesion of the prepared product, and organic borosiloxane is introduced to enhance the self-healing performance of the product.

[0008] Furthermore, the specific preparation process of step S1 is as follows: under an inert atmosphere, preferably a nitrogen atmosphere, octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, an initiator and a hexamethyldisiloxane end-capping agent are added to a reactor, the temperature is increased to 110-130°C for reaction for 3-5 hours, and then the temperature is increased to 140-150°C for reaction for 1-2 hours. After the reaction is completed, the reaction product is dissolved and precipitated 3-5 times using dichloromethane and methanol and then dried to obtain the polysiloxane with a branched ethylene structure; wherein the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, initiator and hexamethyldisiloxane end-capping agent is 120-130:6.8-8.5:0.1:0.11-0.15; and the drying conditions are: vacuum drying in a vacuum drying oven at 50-60°C for 14-20 hours.

[0009] Furthermore, the preparation process of the initiator is as follows: adding tetramethylammonium hydroxide solution and octamethylcyclotetrasiloxane monomer into a reactor, heating to 40-50° C., removing water under vacuum conditions for 1-2 hours, the vacuum degree is -0.1MPa, and after removing water, the reaction system is replaced with nitrogen for 3-5 times, and then the temperature is increased to 85-95° C. for polymerization, and the heating is stopped after the reaction for 12-16 hours, and the temperature is lowered to room temperature, and then anhydrous toluene is added to the reactor to obtain the initiator; wherein the mass ratio of the tetramethylammonium hydroxide solution, the octamethylcyclotetrasiloxane monomer and the anhydrous toluene is 0.42-0.52:10:22-32; and the mass fraction of the tetramethylammonium hydroxide solution is 25wt%.

[0010] Further, the specific preparation process of step S2 is as follows: in an inert atmosphere, preferably a nitrogen atmosphere, a polysiloxane with a branched ethylene structure, toluene and a photoinitiator benzoin dimethyl ether are added to a reactor, mixed evenly, and then mercapto acid is added thereto, and after the addition is completed, it is irradiated with an ultraviolet lamp. After the reaction is completed, tetrahydrofuran and methanol are used for dissolution-precipitation 3-5 times and then dried to obtain the alkyl branched polysiloxane; wherein the polysiloxane with a branched ethylene structure, toluene, a photoinitiator and mercapto acid are added thereto. The mass ratio of the thiol acid is 1-1.5:4-6:0.01:1.2-2.4; the drying condition is vacuum drying at 75-95° C. in a vacuum drying oven for 14-20 hours; the ultraviolet lamp irradiation condition is 365 nm, 120 W, irradiation for 20-40 minutes; the mercapto acid is any one of 4-mercaptobutyric acid, 5-mercaptopentanoic acid, 6-mercaptohexanoic acid, 8-mercaptooctanoic acid, 11-mercaptoundecanoic acid, 14-mercaptotetradecanoic acid, and 16-mercaptohexadecanoic acid, or a mixture of several of them.

[0011] Further, the specific preparation process of step S3 is as follows: add dichloromethane, alkyl branched polysiloxane and polyetheramine into the reactor, control the temperature at 0-4°C, add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and stir for 6-10 minutes after mixing evenly, then stir at room temperature for 18-25 hours, add the same volume of dichloromethane, then wash with dilute hydrochloric acid, water and sodium bicarbonate aqueous solution in sequence, and dry the organic phase with magnesium sulfate to obtain the Siloxane modified polyetheramine; wherein the mass ratio of dichloromethane (the total amount of dichloromethane added twice), alkyl branched polysiloxane, polyetheramine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 80-120:7-15:4-12:2-5, the concentration of dilute hydrochloric acid is 0.5M, the concentration of sodium bicarbonate solution is 4%, and the volume ratio of dichloromethane (the total volume of dichloromethane added twice), dilute hydrochloric acid, water and sodium bicarbonate aqueous solution is 6:4:2:3.

[0012] Polysiloxane has an inorganic silicon-oxygen main chain structure and a combination of organic groups connected to silicon atoms - it has a special semi-inorganic and semi-organic molecular structure. The siloxane part of its molecule is easy to react chemically with the hydroxyl group on the surface of the inorganic material to form a stable silicon-oxygen bond, thereby achieving a firm bond with the inorganic material. At the same time, the organic functional group in the molecule can interact with the organic material to further enhance the bonding strength with the organic material. Therefore, polysiloxane is used to modify polyamide and used in the preparation of hot melt adhesive to improve the viscosity of the hot melt adhesive. However, although polysiloxane has extremely high molecular chain flexibility and structural regularity, it has a low glass transition temperature, which also makes it easy for polysiloxane to crystallize at low temperature before the glass transition temperature, making it difficult to meet the special low-temperature environment application requirements. Since the better the flexibility of the polymer molecular chain, the stronger its activity ability at low temperature and the better the low-temperature resistance, at the same time, by adjusting the structure of the molecular chain, the regularity of the molecular chain can be destroyed to inhibit low-temperature crystallization. The alkyl molecular chain is composed of carbon atoms and hydrogen atoms, and the carbon atoms are connected by single bonds. The internal rotation barrier of this single bond is small, which makes the flexibility of the entire chain better. In addition, the bond length and bond angle between the carbon atoms in the alkyl chain also make the molecular chain easier to bend and twist, thereby showing good flexibility. Therefore, in this application, a polysiloxane with a branched ethylene structure is synthesized, and then a mercapto acid containing a flexible alkyl molecular chain is reacted with an efficient mercapto-ene click reaction to introduce a flexible alkyl branch chain into the side chain of the polysiloxane to make it have a certain low temperature resistance.

[0013] Furthermore, the preparation method of the organic borosiloxane polymer is: placing hydroxy silicone oil in an aluminum beaker, and placing it on a constant temperature magnetic stirrer, raising the temperature to 100-105°C, adding pretreated boric acid thereto in small amounts and multiple times, after the addition is completed, raising the temperature to 120-125°C, and raising it to 150-155°C with sufficient stirring, and keeping it warm for 15-25 minutes to obtain the organic borosiloxane polymer.

[0014] The organosilicon boroxane is synthesized by dehydration condensation between the silanol group at the end of the hydroxyl-terminated polydimethylsiloxane molecular chain and the boron hydroxyl group of boric acid. Since its molecular chain contains more Si-O-Si structures, the bond length of the Si-O bond is longer, and the steric hindrance and rotation barrier are lower, so its molecular chain presents good flexibility. The boron atom with a vacancy can act as an acceptor of the lone electron pair of the oxygen atom in the adjacent molecular chain, forming a non-bonded complex between molecules. The interaction between boron and oxygen atoms can cause dynamic physical crosslinking between molecular chains. The bonding action is in a dynamic process of continuous dissociation and re-formation, which makes it have excellent self-repairing properties. When damaged, the molecular chains can be entangled with each other, and the dynamic reversible boron oxygen bond and dynamic hydrogen bond can be rebonded at room temperature without any external stimulation, thereby realizing rapid self-repair of the damaged part. In addition, in the process of mixing with the polymer, the Si-O-Si structure contained in the polymer can be cross-linked with the Si-O-Si structure contained in the organosilicon boroxane, thereby forming a three-dimensional silicon oxide network structure, further increasing the mechanical properties of the prepared hot melt adhesive.

[0015] The present invention also provides a fast-curing bio-based hot melt adhesive, which is obtained by using the preparation method of any one of the above technical solutions.

[0016] The present invention has the following excellent effects: Dimer acid is used as the main bio-based raw material, which has good biodegradability and is environmentally sustainable. Synthetic polysiloxane with branched ethylene structure and mercapto acid containing flexible alkyl molecular chain are used to introduce flexible alkyl branched chains into the polysiloxane side chain through efficient mercapto-ene click reaction, so as to further improve the low temperature resistance of the hot melt adhesive. At the same time, organic borosiloxane with self-healing properties is added in the preparation process of the hot melt adhesive. When damaged, the molecular chains can be entangled with each other, and the dynamic reversible boron oxygen bonds and dynamic hydrogen bonds can be rebonded at room temperature without any external stimulation, thereby achieving rapid self-repair of the damaged parts. In the process of mixing with the polymer, the Si-O-Si structures contained in different molecular chains are cross-linked to form a three-dimensional silicon oxide network structure, which further increases the mechanical properties of the hot melt adhesive. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0018] The dimer acid used in the present invention (industrial product, monoacid content 3%, dimer content 85%, trimer content 12%, relative molecular mass 560) was purchased from Jinan Zhuobang Economic and Trade Co., Ltd., octamethylcyclotetrasiloxane (purity 98%), tetramethyltetravinylcyclotetrasiloxane (purity 96.5%), tetramethylammonium hydroxide (purity 25wt%), benzoin dimethyl ether (purity 98%) were purchased from Anaiji Chemical & 3A, hexamethyldisiloxane (purity 99%) was purchased from McLean, dichloromethane (analytical grade AR), toluene (pure 99%) was purchased from Xilong Science, 8-mercaptooctanoic acid (purity ≥ 95%), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (purity ≥ 95%), polyetheramine (D-400), sebacic acid (analytical grade), and stearic acid (purity ≥ 98.5%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., hydroxy silicone oil (analytical grade, 2.4%) was purchased from Changzhou Juyou New Material Technology Co., Ltd., and boric acid (analytical grade) was purchased from Tianjin Hengxing Chemical Reagent Manufacturing Co., Ltd. All reagents were commercially available.

[0019] Embodiment 1 A method for preparing a fast-curing bio-based hot melt adhesive comprises the following steps: S1. Under a nitrogen atmosphere, octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, an initiator and a hexamethyldisiloxane end-capping agent are added to a reactor, the temperature is raised to 120° C. for reaction for 4 hours, and then the temperature is raised to 145° C. for reaction for 2 hours. After the reaction is completed, the reaction product is dissolved and precipitated 4 times using dichloromethane and methanol and then dried to obtain a polysiloxane with a branched ethylene structure; wherein the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, initiator and hexamethyldisiloxane end-capping agent is 120:7.2:0.1:0.12; the drying conditions are: vacuum drying in a vacuum drying oven at 55° C. for 16 hours; The preparation process of the initiator is as follows: adding tetramethylammonium hydroxide solution and octamethylcyclotetrasiloxane monomer into a reactor, heating to 45°C, removing water under vacuum conditions for 2 hours, the vacuum degree is -0.1MPa, replacing the reaction system with nitrogen 4 times after removing water, and then raising the temperature to 90°C for polymerization, stopping heating after 14 hours of reaction, and lowering the temperature to room temperature, keeping the reactor sealed, and then adding anhydrous toluene to the reactor to obtain an initiator; wherein the mass ratio of tetramethylammonium hydroxide solution, octamethylcyclotetrasiloxane monomer and anhydrous toluene is 0.48:10:25; the mass fraction of tetramethylammonium hydroxide solution is 25wt%; S2. In a nitrogen atmosphere, polysiloxane with a branched ethylene structure, toluene and a photoinitiator, benzoin dimethyl ether, are added to a reactor, mixed evenly, and then mercapto acid is added thereto. After the addition is completed, the mixture is irradiated with an ultraviolet lamp. After the reaction is completed, tetrahydrofuran and methanol are used for dissolution-precipitation 4 times and then dried to obtain an alkyl branched polysiloxane; wherein the mass ratio of the polysiloxane with a branched ethylene structure, toluene, the photoinitiator and the mercapto acid is 1.2:5:0.01:1.6; wherein the drying condition is vacuum drying at 85°C in a vacuum drying oven for 18h; the ultraviolet lamp irradiation condition is: 365nm, 120W, irradiation for 30min; the mercapto acid is 8-mercaptooctanoic acid; S3, adding dichloromethane, alkyl branched polysiloxane and polyetheramine to the reactor, controlling the temperature at 0°C, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide after mixing evenly, stirring for 8min, and then stirring at room temperature for 22h, adding the same volume of dichloromethane thereto, and then washing with dilute hydrochloric acid, water and sodium bicarbonate aqueous solution in sequence, and drying the organic phase with magnesium sulfate to obtain siloxane-modified polyetheramine; wherein the mass ratio of dichloromethane (the total amount of dichloromethane added twice), alkyl branched polysiloxane, polyetheramine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 110:12:8:3, the concentration of dilute hydrochloric acid is 0.5M, the concentration of sodium bicarbonate solution is 4%, and the volume ratio of dichloromethane (the total volume of dichloromethane added twice), dilute hydrochloric acid, water and sodium bicarbonate aqueous solution is 6:4:2:3; S4, 350 parts by weight of dimer acid, 25 parts by weight of sebacic acid, 65 parts by weight of siloxane-modified polyetheramine, 8 parts by weight of antioxidant 2,6-di-tert-butyl-4-methylphenol and 1.2 parts by weight of catalyst bismuth isooctanoate are added to the reactor, stirred and heated to 120°C, the stirring rate is 250rpm, and 38 parts by weight of ethylenediamine are added thereto, and the heating is turned off to allow it to heat up naturally. Ethylenediamine is added dropwise, the dropwise addition time is controlled for 60 minutes, and the temperature is controlled at 140°C. After the addition is completed, the temperature is controlled at 140°C for 2 hours, and then the temperature is increased to 240°C for 30 minutes; S5, after the heat preservation, vacuum polymerization is carried out, the vacuum degree is controlled below -0.092MPa, the vacuum time is 30min, and after the polymerization is completed, nitrogen is used to break the air, the temperature is lowered and the material is discharged, and the cooling rate is 5°C / min to obtain a polymer; S6. Add 450 parts by weight of polymer and 18 parts by weight of organoborosiloxane into a reaction kettle, heat to 120°C, stir and react for 2 hours, add 4 parts by weight of stearic acid and control the vacuum degree to -0.095 MPa, vacuum and stir for 30 minutes, cool and discharge to obtain a fast-curing bio-based hot melt adhesive.

[0020] Among them, the preparation method of the organic borosiloxane polymer is: 65 parts by weight of hydroxyl silicone oil are placed in an aluminum beaker, and the beaker is placed on a constant temperature magnetic stirrer, and the temperature is raised to 105°C, and 1.8 parts by weight of pretreated boric acid are added thereto in small amounts and multiple times, and the addition is divided into 6 times, each time with an interval of 10 minutes. After the addition is completed, the temperature is raised to 125°C, and then raised to 155°C with sufficient stirring, and kept warm for 20 minutes to obtain an organic borosiloxane polymer; the pretreatment process of boric acid is: the boric acid is placed in a mortar and ground for 35 minutes.

[0021] Embodiment 2 Compared with the first embodiment, this embodiment has the following differences: In step S1, octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, an initiator and a hexamethyldisiloxane end-capping agent are added to a reactor, and the temperature is raised to 110° C. for reaction for 3 hours, and then the temperature is raised to 140° C. for reaction for 1 hour. After the reaction is completed, the reaction product is dissolved and precipitated 3 times using dichloromethane and methanol and then dried; wherein the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, initiator and hexamethyldisiloxane end-capping agent is 120:6.8:0.1:0.11; and the drying conditions are: vacuum drying in a vacuum drying oven at 50° C. for 14 hours.

[0022] During the preparation of the initiator, tetramethylammonium hydroxide solution and octamethylcyclotetrasiloxane monomer were added to the reactor, heated to 40°C, and dehydrated under vacuum for 1 hour. After dehydration, the reaction system was replaced with nitrogen three times, and then the temperature was raised to 85°C for polymerization. The heating was stopped after the reaction for 12 hours; wherein the mass ratio of tetramethylammonium hydroxide solution, octamethylcyclotetrasiloxane monomer and anhydrous toluene was 0.42:10:22.

[0023] In step S2, after the reaction is completed, tetrahydrofuran and methanol are used for dissolution-precipitation three times and then dried. The mass ratio of polysiloxane with a branched vinyl structure, toluene, photoinitiator and mercapto acid is 1:4:0.01:1.2; the drying condition is vacuum drying at 75°C in a vacuum drying oven for 14 hours; the ultraviolet lamp irradiation conditions are: 365nm, 120W, and irradiation for 20 minutes.

[0024] In step S3, dichloromethane, alkyl branched polysiloxane and polyetheramine are added to the reactor, the temperature is controlled at 2°C, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added after mixing evenly, and stirred for 6 minutes, and then stirred at room temperature for 18 hours, wherein the mass ratio of dichloromethane (the total amount of dichloromethane added twice), alkyl branched polysiloxane, polyetheramine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 80:7:4:2.

[0025] In step S4, 250 parts by weight of dimer acid, 12 parts by weight of sebacic acid, 25 parts by weight of siloxane-modified polyetheramine, 3 parts by weight of antioxidant 2,6-di-tert-butyl-4-methylphenol and 0.6 parts by weight of catalyst bismuth isooctanoate are added to a reactor, stirred and heated to 110°C, with a stirring rate of 200 rpm. When 28 parts by weight of ethylenediamine are added thereto, the heating is turned off. When ethylenediamine is added, the dripping time is controlled for 50 minutes and the temperature is controlled at 130°C. After the addition is completed, the temperature is controlled at 130°C for 1 hour, and then the temperature is increased to 230°C and maintained for 20 minutes.

[0026] In step S5, the vacuuming time is 20 minutes, and the cooling rate during the cooling and discharging is 5°C / min.

[0027] In step S6, 260 parts by weight of polymer and 8 parts by weight of organoborosiloxane are added to a reaction kettle, heated to 110°C, stirred for reaction for 1 hour, 1.2 parts by weight of stearic acid are added and the vacuum degree is controlled to -0.095 MPa, and vacuumed and stirred for 20 minutes.

[0028] The rest are all referred to Example 1.

[0029] Embodiment 3 Compared with the first embodiment, this embodiment has the following differences: In step S1, octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, an initiator and a hexamethyldisiloxane end-capping agent are added to a reactor, and the temperature is raised to 130° C. for reaction for 5 hours, and then the temperature is raised to 150° C. for reaction for 2 hours. After the reaction is completed, the reaction product is dissolved and precipitated 5 times using dichloromethane and methanol and then dried; wherein the molar ratio of octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, initiator and hexamethyldisiloxane end-capping agent is 130:8.5:0.1:0.15; and the drying conditions are: vacuum drying at 60° C. in a vacuum drying oven for 20 hours.

[0030] During the preparation of the initiator, tetramethylammonium hydroxide solution and octamethylcyclotetrasiloxane monomer were added to the reactor, heated to 50°C, and dehydrated for 2 hours under vacuum conditions. After dehydration, the reaction system was replaced with nitrogen 5 times, and then the temperature was raised to 95°C for polymerization. The heating was stopped after the reaction for 16 hours; wherein the mass ratio of tetramethylammonium hydroxide solution, octamethylcyclotetrasiloxane monomer and anhydrous toluene was 0.52:10:32.

[0031] In step S2, after the reaction is completed, tetrahydrofuran and methanol are used for dissolution-precipitation 5 times and then dried, and the mass ratio of polysiloxane with a branched vinyl structure, toluene, photoinitiator and mercapto acid is 1.5:6:0.01:2.4; the drying condition is vacuum drying at 95°C in a vacuum drying oven for 20 hours; the ultraviolet lamp irradiation conditions are: 365nm, 120W, and irradiation for 40 minutes.

[0032] In step S3, dichloromethane, alkyl branched polysiloxane and polyetheramine are added to the reactor, the temperature is controlled at 4°C, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is added after mixing evenly, and stirred for 10 minutes, and then stirred at room temperature for 25 hours, wherein the mass ratio of dichloromethane (the total amount of dichloromethane added twice), alkyl branched polysiloxane, polyetheramine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 120:15:12:5.

[0033] In step S4, 400 parts by weight of dimer acid, 28 parts by weight of sebacic acid, 72 parts by weight of siloxane-modified polyetheramine, 12 parts by weight of antioxidant 2,6-di-tert-butyl-4-methylphenol and 1.8 parts by weight of catalyst bismuth isooctanoate are added to a reactor, stirred and heated to 130°C, with a stirring rate of 300 rpm. When 42 parts by weight of ethylenediamine are added thereto, the heating is turned off. When ethylenediamine is added, the dripping time is controlled for 70 minutes and the temperature is controlled at 150°C. After the addition is completed, the temperature is controlled at 150°C for 2 hours, and then the temperature is increased to 250°C for 40 minutes.

[0034] In step S5, the vacuuming time is 40 minutes, and the cooling rate during the cooling and discharging is 10°C / min.

[0035] In step S6, 520 parts by weight of polymer and 25 parts by weight of organoborosiloxane are added to a reaction kettle, heated to 130°C, stirred for reaction for 3 hours, 6 parts by weight of stearic acid are added and the vacuum degree is controlled to -0.095 MPa, and vacuumed and stirred for 40 minutes.

[0036] The rest are all referred to Example 1.

[0037] Comparative Example 1 Compared with Example 1, in the preparation process of step S2, the mercapto acid is replaced with 4-mercaptobutyric acid, and the rest is the same as Example 1.

[0038] Comparative Example 2 Compared with Example 1, in the preparation process of step S2, the mercapto acid is replaced with 5-mercaptopentanoic acid, and the rest is the same as Example 1.

[0039] Comparative Example 3 Compared with Example 1, in the preparation process of step S2, the mercapto acid is replaced with 6-mercaptohexanoic acid, and the rest is the same as Example 1.

[0040] Comparative Example 4 Compared with Example 1, in the preparation process of step S2, the mercapto acid is replaced with 11-mercaptoundecanoic acid, and the rest is the same as Example 1.

[0041] Comparative Example 5 Compared with Example 1, in the preparation process of step S2, the mercapto acid is replaced with 14-mercaptotetradecanoic acid, and the rest is the same as Example 1.

[0042] Comparative Example 6 Compared with Example 1, in the preparation process of step S2, the mercapto acid is replaced with 16-mercaptohexadecanoic acid, and the rest is the same as Example 1.

[0043] Comparative Example 7 Compared with Example 1, this comparative example uses vinyl-terminated dimethyl polysiloxane and polyetheramine to modify the polyetheramine, and the rest is referred to Example 1, which is as follows: A method for preparing a bio-based hot melt adhesive comprises the following steps: A1. Add vinyl-terminated dimethyl polysiloxane and polyetheramine into a reactor, heat to 65° C., and stir and mix for 20 minutes to obtain vinyl-terminated dimethyl polysiloxane-modified polyetheramine; A2, referring to step S4 in Example 1, wherein the siloxane-modified polyetheramine is replaced with a vinyl-terminated dimethylpolysiloxane-modified polyetheramine; A3, refer to step S5 in embodiment 1; A4. Refer to step S6 in embodiment 1.

[0044] Comparative Example 8 Compared with Example 1, this comparative example does not modify the polyetheramine, and the rest is referred to Example 1, as follows: A method for preparing a bio-based hot melt adhesive comprises the following steps: B1, referring to step S4 in Example 1, wherein the siloxane-modified polyetheramine is replaced with polyetheramine; B2, refer to step S5 in embodiment 1; B3. Refer to step S6 in embodiment 1.

[0045] Comparative Example 9 Compared with Example 1, this comparative example does not modify the polyetheramine, and does not add the organoborosiloxane polymer during the preparation process. The rest is referred to Example 1, as follows: A method for preparing a bio-based hot melt adhesive comprises the following steps: B1, referring to step S4 in Example 1, wherein the siloxane-modified polyetheramine is replaced with polyetheramine; B2, refer to step S5 in embodiment 1; B3. Refer to step S6 in Example 1, except that no organoborosiloxane is added.

[0046] Related tests: Tensile strength and elongation test: The samples prepared in each embodiment and comparative example were made into dumbbell shape according to standard ASTM-D638-2003, and the tensile performance and low-temperature flexibility tests were performed after measuring the thickness, wherein the low-temperature flexibility is the limit temperature value at which the fracture occurs in the unstretched state, and the low-temperature fracture elongation is the tensile elongation at a temperature of -50°C. The test results are shown in Table 1.

[0047] Table 1 Test results of low temperature flexibility, tensile strength and elongation at break Open time test method: With reference to HG / T 3716-2003 Determination of open time of hot melt adhesive, the samples prepared in each embodiment and comparative example were tested. The test was carried out in an environment with a temperature of 23°C ± 2°C and a relative humidity of 50% ± 5%. The hot melt adhesive melt temperature was 150°C ± 2°C, and the test interval was 5s. The test results are shown in Table 2, wherein the shorter the open time, the better the quick-drying property of the hot melt adhesive.

[0048] Table 2 Opening time test results Tensile shear strength test: The samples prepared in each embodiment and comparative example were used for bonding between wooden boards and between PE boards and PET boards. After two groups of samples were prepared, the tensile shear strength between the samples and different substrates in the two groups of samples was tested with reference to GB / T 7124-2008 "Determination of tensile shear strength of adhesives (rigid material to rigid material)". The tensile rate was 10 mm / min, and the low-temperature (-40°C) tensile shear strength refers to cooling to low temperature (-40°C) after the composite is completed, and then testing at low temperature (-40°C). The test results are shown in Table 3, wherein the higher the tensile shear strength, the higher the bonding strength of the hot melt adhesive to the substrate, and the better the bonding performance.

[0049] Table 3 Tensile shear strength test results It can be found from the test results in Table 3 that in the test results of Example 1 and Comparative Examples 1 to 6, the tensile shear strength increases with the growth of the mercapto acid flexible chain, but its performance decreases as the flexible chain continues to grow. This is because as the length of the flexible alkyl chain increases, the excessively long flexible alkyl chain is prone to cause intramolecular crosslinking, resulting in a decrease in performance.

[0050] Self-repairing performance test: The sample prepared in Example 1 was made into a dumbbell shape according to the standard ASTM-D638-2003, and a double-layer blade was prepared using a utility blade (100×18×0.5 mm). A weight of 100 g was placed on the double blade to control the applied force, and a cut was produced under the action of gravity. The repair of the scratches on the sample surface was observed using a LEXTOLS4000 laser confocal microscope produced by OLYMPUS of Japan. The test results are shown in Table 4, where the average value of the absolute value of the height difference at each point is used to characterize the surface roughness of the sample, and S α It can be seen from the test results that as time goes by, the roughness of the cut produced on the sample prepared in Example 1 gradually decreases, which indicates that the prepared sample has a certain healing performance without external force.

[0051] Table 4 Self-repair performance test results It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0052] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a fast-curing bio-based hot melt adhesive, characterized in that: The following steps are involved: S1, obtaining a polysiloxane with a branched vinyl structure by a ring-opening polymerization reaction of cyclosiloxane; S2, polysiloxane with branched vinyl structure and mercapto acid are reacted by mercapto-ene click reaction to obtain polysiloxane containing alkyl branches; S3, alkyl branched polysiloxane and polyetheramine are subjected to amidation reaction to obtain siloxane-modified polyetheramine; S4, adding dimer acid, sebacic acid, siloxane-modified polyetheramine, antioxidant and catalyst into the reaction kettle, stirring and heating to 110-130°C, adding ethylenediamine and turning off the heating, after the addition is completed, controlling the temperature at 130-150°C for 1-2h, and then raising the temperature to 230-250°C for 20-40min; S5, after the heat preservation is completed, vacuum polymerization is carried out, and after the polymerization is completed, nitrogen is used to break the air, and the temperature is lowered to discharge the material to obtain a polymer; S6. Add the polymer and organoborosiloxane into a reaction kettle, heat to 110-130° C., stir and react for 1-3 hours, add stearic acid and control the vacuum degree, vacuum and stir for 20-40 minutes, cool and discharge, and obtain the fast-curing bio-based hot melt adhesive.

2. The method for preparing the fast-curing bio-based hot melt adhesive according to claim 1, characterized in that: The specific preparation process of step S1 is as follows: under an inert atmosphere, octamethylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, an initiator and a hexamethyldisiloxane end-capping agent are added to a reactor, the temperature is increased to 110-130° C. for reaction for 3-5 hours, and then the temperature is increased to 140-150° C. for reaction for 1-2 hours. After the reaction is completed, the polysiloxane with a branched vinyl structure is obtained by dissolving and precipitating with dichloromethane and methanol for 3-5 times and then drying.

3. The method for preparing the fast-curing bio-based hot melt adhesive according to claim 2, characterized in that: The preparation process of the initiator is as follows: adding tetramethylammonium hydroxide solution and octamethylcyclotetrasiloxane monomer into a reactor, heating to 40-50°C, removing water under vacuum conditions for 1-2 hours, replacing the reaction system with nitrogen after removing water, and then raising the temperature to 85-95°C for polymerization, stopping heating after reacting for 12-16 hours, and lowering the temperature to room temperature, and then adding anhydrous toluene into the reactor to obtain the initiator.

4. The method for preparing the fast-curing bio-based hot melt adhesive according to claim 1, characterized in that: The specific preparation process of step S2 is as follows: under an inert atmosphere, polysiloxane with a branched vinyl structure, toluene and a photoinitiator are added to a reactor, mixed evenly, and then mercapto acid is added thereto. After the addition is completed, it is irradiated with an ultraviolet lamp. After the reaction is completed, it is dissolved and precipitated 3-5 times with tetrahydrofuran and methanol and then dried to obtain the alkyl branched polysiloxane.

5. The method for preparing the fast-curing bio-based hot melt adhesive according to claim 4, characterized in that: The drying conditions after dissolution and precipitation with tetrahydrofuran and methanol for 3-5 times are 75-95° C. in a vacuum drying oven for 14-20 hours.

6. The method for preparing the fast-curing bio-based hot melt adhesive according to claim 1, characterized in that: The specific preparation process of step S3 is as follows: add dichloromethane, alkyl branched polysiloxane and polyetheramine into a reactor, control the temperature at 0-4°C, add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and stir for 6-10 minutes after mixing evenly, then stir at room temperature for 18-25 hours, add dichloromethane, then wash with dilute hydrochloric acid, water and sodium bicarbonate aqueous solution in sequence, and dry the organic phase with magnesium sulfate to obtain the siloxane-modified polyetheramine.

7. The method for preparing the fast-curing bio-based hot melt adhesive according to claim 1, characterized in that: The preparation method of the organic borosiloxane polymer is as follows: hydroxy silicone oil is placed in an aluminum beaker, and the beaker is placed on a constant temperature magnetic stirrer, and the temperature is raised to 100-105° C., and pre-treated boric acid is added thereto in small amounts and multiple times. After the addition is completed, the temperature is raised to 120-125° C., and then raised to 150-155° C. with sufficient stirring, and kept warm for 15-25 minutes to obtain the organic borosiloxane polymer.

8. A fast-curing bio-based hot melt adhesive, characterized in that: The fast-curing bio-based hot melt adhesive is obtained by the preparation method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • A kind of reactive polyurethane hot melt adhesive and preparation method thereof

    CN115725259B

  • Reactive polyurethane hot melt adhesive for bonding nitrile rubber and preparation method thereof

    CN115851213B

  • Wear-resistant polyamide hot-melt adhesive and preparation method thereof

    CN106893098A

  • Recyclable self-repairing flexible compliant electrode and preparation method thereof

    CN112898779A

  • Copolyamide hot melt adhesive and preparation method thereof

    CN119119951A